Post Caesarean necrotizing soft tissue infection leading to maternal death: a case report - Abdullah, Saba; Khan, Fiza Ali; Usman; Anbreen, Tayyeba; Hossain, Nazli (Journal of the Pakistan Medical Association, 2022)
Necrotizing soft tissue infection is lethal and can lead to sepsis, multi-organ failure, and death. Here we describe a case, which reported to us within 24 hours of Caesarean section, with acute abdominal pain, tachycardia, and tachypnoea. Local examination revealed a large area of necrotic subcutaneous tissue involving a Caesarean section scar. Immediate debridement was carried out and repeated twice after the initial procedure but she could not survive. Keywords: Necrotizing soft tissue infection, Cesarean section, Prolonged Labor, Diabetes mellitus.